Small engine repair [videorecording (DVD)] - Pollono, John; Pollono, John; Pollono, John; Bernthal, Jon; Bernthal, Jon; Whigham, Shea, 1969-; Spiro, Jordana; Pollono, John (Vertical Entertainment, 2021)
When a mechanic invites a couple friends to his repair shop, the arrival of a young man reveals another agenda, and events begin to spiral out of control.